2017
DOI: 10.9790/0853-1603088388
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of HCV Infection among Haemodialysis Patients at Dialysis Centers in Khartoum State - Sudan

Abstract: Hepatitis C virus share razors. P values = (0.0001, 0.0031, 0.0001, 0.0018, 0.0005 and 0.0002) Results: Field workers interviewed ten dialysis centers with a total of 287 study subjects. Sixty out of 287 (20.9%) was found to be anti-HC reactive. The multivariate analysis indicated as risk factors associated to anti-HCV positivity the number of blood transfusion received, duration of dialysis treatment, number of units of treatment, history of surgeries, multiple injections and using

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
1
0
1
Order By: Relevance
“…On the other hand, the prevalence of HBV among HD patients was estimated to be (0–6.6%) in developed countries [ 24 ]. Our results are similar to previous studies from other developing Arab countries where the prevalence rates of HBV and HCV were showed to be 3% and 21.7% respectively in Yemen [ 12 ] and about 20.9% of the overall HD patients were infected with HCV in Sudan [ 25 ]. However, the prevalence rates of HBV/HCV in our study were higher than those reported from neighboring countries such as Lebanon (1.6%:4.7%) [ 26 ], Iraq ( 3.2%/3.4%) [ 7 ], and Palestine (3.8%/7.4%) [ 5 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, the prevalence of HBV among HD patients was estimated to be (0–6.6%) in developed countries [ 24 ]. Our results are similar to previous studies from other developing Arab countries where the prevalence rates of HBV and HCV were showed to be 3% and 21.7% respectively in Yemen [ 12 ] and about 20.9% of the overall HD patients were infected with HCV in Sudan [ 25 ]. However, the prevalence rates of HBV/HCV in our study were higher than those reported from neighboring countries such as Lebanon (1.6%:4.7%) [ 26 ], Iraq ( 3.2%/3.4%) [ 7 ], and Palestine (3.8%/7.4%) [ 5 ].…”
Section: Discussionsupporting
confidence: 92%
“…Other risk factors reported by other studies such as history of blood transfusion [ 15 , 34 ], history of surgery [ 25 , 36 ], and male sex [ 12 ] were not significantly associated with HCV prevalence among our study patients. However, the risk factors for HCV infection among HD patients varies notably between countries.…”
Section: Discussioncontrasting
confidence: 43%